Women in Panchayati Raj Institutions - Kumar Jha,Ashok (Anmol Publication, 2004)
To study the problems and prospects of women in the changing rural social and political system is the need of today?s system. Because women consist of 48.9 per cent of the population and after all governmental and non-governmental efforts their position is not improving equally to men. Panchayati Raj Institutions opened a vast opportunity for the development and progress of rural women, especially 50 per cent reservation through Bihar Panchayati Raj Act, 2006 had made village women and society to rethink their role in political and social field. The rural women in Bihar are subjected to discrimination, operation, subordination and exploitation. Through the institutions of Panchayati Raj they can prove themselves strong in the society and these types of operation can be removed. This book is an effort to become an example and guideline for their problems and prospects.